PENENTUAN KANDUNGAN LOGAM Cd DAN Cu DALAM PRODUK IKAN KEMASAN KALENG SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Hellna Tehubijuluw; Eirene.G. Fransina; Semuel Simra Pada (Magister Program of Applied Chemistry, Udayana University, Bali-INDONESIA, 2013)
Determination of cadmium and copper concentration of canned fish have been done. Some canned fished were taken away from three mercks circulating in a market and marked as RS (the 1st sample), NF(2nd sample), and CP(3rd sample). The aim of this research is to determine of cadmium (Cd) and copper (Cu) content of canned fish and to compare the content with the standard limit regulated by the Directorate General of Drug and Food Control No: 03725/B/SK/VII/89. Determination of metal concentration was conducted using atomic absorption spectrophotometer (AAS). It was found that Cd concentrations of RS and NF samples are 0.1969 mg/kg and0.0448 mg/kg, respecively while for CP it was not detected. For Cu concentrations of RS, NF, and CP are 3.3303 mg/kg, 4.6130 mg/kg, 3.3047 mg/kg respectively. The results indicated that the samples of the canned fishes have been contaminated with Cd and Cu metals although the levels of those metals are still lower than the maximum limit regulated by the Directorate General of Drug and Food Control No: 03725/B/SK/VII/89 where the maximum limit for Cd and Cu are 0,2 mg.kg and 5.0 mg/kg respectively.